Dekonstruksi Sungkun sebagai Medium Identitas Perempuan Kerinci - Amelia, Olenda; Wastap, Jaeni (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2025)
This study explores sungkun as one of the traditional clothing attributes worn by Kerinci women in Jambi Province, conceptualized as a cultural text that stitches together identity, values, and social structure through the female body. In Kerinci tradition, sungkun functions not merely as attire, but as a symbolic layer that regulates how the female body is presented, interpreted, and governed within the context of custom, spirituality, and social relations. Using a descriptive qualitative approach and symbolic ethnography method, this research investigates the meanings embedded in the visual elements of sungkun and its usage in both ritual and everyday life. The findings reveal that sungkun serves as a performative medium that constructs the identity of women as moral guardians, custodians of tradition, and inheritors of cosmological values. Through a deconstructive lens, the article also reveals the transformation of sungkun’s meaning in contemporary cultural landscapes, as it undergoes resemanticization through performing arts, cultural festivals, and visual media. Thus, sungkun becomes a space of negotiation between traditional heritage and modern identity expression among Kerinci women. This article contributes to the fields of art, culture, and gender studies by offering a renewed reading of textile artifacts as symbolic texts and the body as a narrative medium.